When Ants Move Mountains: Uncovering a Media Theory of Human Agency - Patricia W. Elliott (KOME: An International Journal of Pure Communication Inquiry)
Just as Smythe argued communication was the “blindspot of western Marxism,” western communication and media theorizing itself suffers a blind spot, when it places media power in the hands of dictators and captains of industry as if no others might put pen to paper and change history. Meanwhile, theoretical explorations of how media praxis might be understood and employed for emancipation – not subjugation – emerged through the experiences of people in the Global South and Indigenous communities. This article examines and contrasts the theoretical silos, seeking moments of cross-over and synergy between static, top-down conceptualizations of Western mass media theory, and the more people-powered media praxis of colonized people seeking liberation. Building on the literature of differing experiences, the author draws a framework to encompass the full spectrum of media power. Here scholars, policy planners, and media practitioners alike may find common ground from which to recognize and support grassroots media producers as agents of meaningful social change.